Religious Self-Identification in Ukraine of the Independence Period: Level, Character, Problem, Trends - Klymov, Valeriy Volodymyrovych (Ukrai͏̈ns'ke relihijeznavstvo, 2009)
Problems of modern religiosity, its origin, causes and real level in Ukrainian society; religious self-identification, which in sociological surveys and polls of different levels was usually identified with the true level of religiosity in society; problems of validity and authenticity of religious self-determination of a person and other related problems were started to be considered by scientists (religious scholars, sociologists, cultural scientists) from the late 80's - early 90's of the XX century. mostly as a response to the increasing trend of religiosity in Ukraine. Already in the first half of the 90-ies there are works in which attempts were made to understand the phenomenon of modern religiosity in Ukrainian society, to identify the reasons for the steadily increasing religiosity, at least in general terms to characterize its peculiarities. Notwithstanding the huge number of extra-scientific, emotionally-complementary, poorly substantiated methodologically and factually, confessionally biased publications of this period, it should be noted that the scientific progress in the study of modern religiosity was related to the studies of the Institute of Religion NAS of Ukraine, other centers that have directly or indirectly studied the functioning of religion and the church in modern society.